Radiological characterization of printed circuit boards for future elimination. (July 2016) - Zaffora, Biagio; Magistris, Matteo
Abstract: Electronic components like printed circuit boards (PCBs) are commonly used in CERN's accelerator complex. During their lifetime some of these PCBs are exposed to a radiation field of protons, neutrons and pions and are activated. In view of their disposal towards the appropriate final repository, a radiological characterization must be performed. The present work proposes a general characterization procedure based on the definition of a reference chemical composition, on the calculation of the corresponding radionuclide inventory and on the measurement of a tracer radionuclide. This method has been validated with real-life cases of electronic boards which were exposed to the typical radiation fields in CERN's accelerators. The activation studies demonstrate that silver is the key element with respect to the radiological characterization of electronic waste due to the production of Ag-110m and Ag-108m. A sensitivity analysis shows that the waiting time is the main parameter affecting the radionuclide inventory. Results also indicate that, as is the case of other families of radioactive waste, an accurate assessment of the radiological inventory of PCBs would require the precise knowledge of their chemical composition, as well as the radiation field to which they were exposed. Abstract : Highlights: We proposed a general characterization process for activated Printed Circuit Boards (PCBs). Estimated a reference chemical composition for electronic boards. Calculated the radionuclide inventory and the importance of major radionuclides. Identified the chemical composition, the radiation field and the cooling time as sensible parameters for the activation of PCBs. Validated the characterization method with real-life cases of PCBs activated at CERN.